PENGARUH SUPLEMENTASI IKAN TERI (Stolephorus sp.) TERHADAP KANDUNGAN OMEGA-3 DAN OMEGA-6 PADA TELUR DAN DAGING AYAM RAS HISEX BROWN [THE EFFECT OF ANCHOVY FISH (Stolephorus sp.) SUPPLEMENTATION ON THE CONTENT OF OMEGA-3 AND OMEGA-6 IN HISEX BROWN CHICKEN EGG AND MEAT] - Sugata, Marcelia; Wahyudi, Callista Levina; Kodrat, Erlangga; Tan, Jan Tjie (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2021)
The balance between omega-3 and omega-6 in the body is very important. The ideal omega-6/omega-3 ratio is 4:1 or lower, but modern people's diets with high omega-6/omega-3 ratio increase the risk of various diseases such as cardiovascular disease. To lower this ratio, the increase of omega-3 intake is required. Egg as a source of omega-3 is idealy consumed by people. Omega-3 eggs can be increased by providing supplementation of anchovy fish in chicken feed. Therefore, this study aimed to analyse the effect of five-months anchovy (Stolephorus sp.) supplementation on the level of omega-3 and omega-6 in Hisex Brown chicken eggs and meat. Laying hens were fed commercial feed which had been added with anchovy powder for five months. Samples of eggs and chicken meat (breast, upper thigh, lower thigh) were taken every 1-2 months, then the oil from the sample was extracted. Analysis of omega-3 and omega-6 content in oil samples was carried out by GC-MS Based on the results after five months of supplementation, longer supplementation period resulted in higher content of omega-3 (especially docosahexaenoic acid/DHA) and omega-6 (arachidonic acid/ARA) in egg yolks. Compared to the first month, the omega-3 and omega-6 content of eggs in the fifth month increased by 3.5 and 15.5 times, respectively. The content of omega-3 and omega-6 in chicken meat (breast, upper and lower thigh) during supplementation period were fluctuated. However, the omega-6/omega-3 ratios in the chicken breast and upper thighs got lower as the supplementation period lengthened.BAHASA INDONESIA ABSTRAK: Keseimbangan antara omega-3 dan omega-6 di dalam tubuh sangatlah penting. Rasio omega-6/omega-3 yang ideal adalah 4:1 atau lebih rendah, namun pola makan masyarakat modern memiliki rasio omega-6/omega-3 yang tinggi sehingga meningkatkan risiko berbagai penyakit seperti kardiovaskular. Untuk menurunkan rasio tersebut, dibutuhkan peningkatan asupan omega-3. Telur merupakan salah satu sumber omega-3 yang banyak dikonsumsi oleh masyarakat. Peningkatan omega-3 telur dapat dilakukan dengan memberikan suplementasi ikan teri pada pakan ayam. Oleh karena itu, penelitian ini bertujuan untuk menganalisis pengaruh suplementasi ikan teri (Stolephorus sp.) terhadap kandungan omega-3 dan omega-6 pada telur dan daging ayam ras petelur strain Hisex Brown. Ayam petelur diberikan pakan komersil yang telah ditambahkan dengan bubuk ikan teri selama lima bulan. Sampel telur dan daging ayam (dada, paha atas, paha bawah) diambil setiap 1-2 bulan, lalu minyak dari sampel diekstraksi. Analisis kandungan omega-3 dan omega-6 dari sampel minyak dilakukan dengan GC-MS. Berdasarkan hasil yang diperoleh dari lima bulan suplementasi, periode suplementasi yang semakin lama menghasilkan kandungan omega-3 (khususnya docosahexaenoic acid/DHA) dan omega-6 (arachidonic acid/ARA) yang semakin tinggi pada kuning telur. Dibandingkan bulan pertama, kandungan omega-3 dan omega-6 telur pada bulan kelima meningkat masing-masing 3,5 dan 15,5 kali lipat. Kandungan omega-3 dan omega-6 pada daging ayam (dada, paha atas dan paha bawah) selama periode suplementasi mengalami fluktuasi. Meskipun demikian, rasio omega-6/omega-3 pada dada dan paha atas semakin rendah seiring dengan periode suplementasi yang semakin lama.